Spelt: Agronomy, Quality, and Flavor of Its Breads from 30 Varieties Tested across Multiple Environments. Issue 2 (12th January 2017) - Rapp, Matthias; Beck, Heinrich; Gütler, Hermann; Heilig, Wendelin; Starck, Norbert; Römer, Peter; Cuendet, Catherine; Uhlig, Friedrich; Kurz, Hannes; Würschum, Tobias; Longin, C. Friedrich H.
Abstract : Spelt ( Triticum aestivum L. ssp. spelta ) is an old hulled wheat currently receiving renewed interest of consumers, bakers, millers, and farmers. Our objectives were (i) to assess the genetic variability and heritability of agronomic and quality traits together with the flavor and odor of breads, (ii) to investigate correlations among these traits, and (iii) to draw conclusions for spelt breeding targeting improved yield, quality, and flavor of end products. Therefore, we investigated 30 spelt varieties in up to six field locations and determined important agronomic parameters and numerous quality traits, as well as flavor and odor of breads made from all varieties. As for the closely related bread wheat ( T. aestivum L. ssp. aestivum ), protein and gluten content were tightly correlated in spelt, but both were only moderately correlated with protein quality. The correlation between the sedimentation volume determined either with sodium dodecyl sulfate (SDSS) or according to Zeleny was very high ( r = 0.94, p < 0.001). However, SDSS differentiated the spelt varieties better and is thus proposed for future spelt breeding and evaluations. We determined a significant genetic variation for bread flavor with a heritability of 0.56. Furthermore, this flavor was not correlated with traits important for spelt breeding, i.e., protein quality and agronomy. Thus, future breeding can simultaneously target improved yield, bread‐making quality, and a more aromatic bread flavor of new spelt varieties, which would also be of interest for bread and durum wheat ( Triticum durum Desf.). These findings highlight the need of an intensified interdisciplinary research to develop faster methods for flavor and odor evaluation of breads.